Establishing an online training program for pediatric surgery residents during and after the COVID-19 pandemic – lessons learned - Gnatzy, Richard; Schwab-Eckhardt, Benjamin; Brunner, Annika; Drossard, Sabine (GMS Journal for Medical Education)
Aim: During the COVID-19 pandemic, social restrictions significantly impacted post-graduate training in pediatric surgery. This paper describes the implementation and continuation of a German-language, online training program for pediatric surgery residents, named “KiWI” (Kinderchirurgische Weiterbildung im Internet), which was established during the period of social distancing.Method: “KiWI” was designed as a monthly, post-graduate online seminar course that combined practical relevance with theoretical knowledge. The teaching methods included case presentations by residents, active participant engagement through multiple-choice questions, and chat interactions. Course evaluation was conducted via an online questionnaire. The program was specifically tailored to meet the needs of the residents through close collaboration with them.Results: Between February 2021 and September 2023, an average of 53 participants (M=53; SD=20) attended each session, with no correlation observed between attendance and the level of social restrictions. Fifty-seven percent of the participants were residents, with over half being in their fifth year or beyond of post-graduate training. Evaluations indicated a high level of satisfaction with the topics and course design. Lecturers showed great willingness to participate voluntarily, and moderators facilitated the sessions to support the lecturers. Technical issues were addressed through pre-session test runs.Conclusion: The “KiWI” project demonstrates the potential of online continuing education as a resource-efficient supplement to post-graduate medical education. The program achieved high levels of acceptance and accessibility, showcasing the effectiveness of a decentralized online seminar format with interactive, case-based teaching methods.